(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
A deserted reign always suffers from lack of pure water in a large part of its area. In this area, valuable fresh water from swamps or ground water wells is salt water, and it is necessary purified or distillated. In the current experimental study, a new design is made to improve the yield of fresh water of a pyramid solar still by using an immersion type DC- water heater. It investigates the effect of an external fan to cool the glass surface. The Experiment was take placed in the summer season in Iraq conditions at latitude (33.2 ° N). A solar still with 32.5°glass slope angle is chosen in our work. As the productivity of a solar still is more for low water depths, the water level in the bottom basin maintained at 3 cm. The experimental outcomes observed that the yield of fresh water increased by a significant 370% when DC water heater each having 350 W capacities was used. During used the external cooling fan the productivity of fresh water was existed to decrease by (7%) and (15%) for wind speeds of (7 m/s) and (9 m/s) respectively. A good comparison takes placed with other experimental study was taken.